Dietary Supplementation with Green Fruits of Musa spp. AAA Ameliorates Acute, Subchronic, and Chronic Intestinal Inflammation with Relapse Induced by Trinitrobenzenesulfonic Acid in Rats - Batista, Gabriela R. [UNESP]; Quaglio, Ana Elisa Valencise [UNESP]; Almeida Junior, Domingues de [UNESP]; Sassaki, Ligia Yukie [UNESP]; Di Stasi, Luiz Claudio [UNESP] (American Chemical Society (ACS), 2025)
Musa spp. AAA (green dwarf banana) fruit has many health benefits, including intestinal anti-inflammatory activity associated with the presence of resistant starch. Resistant starch is an indigestible polysaccharide source of short-chain fatty acids (SCFAs) after the colon fermentative process by gut microbiota. SCFAs are classified as metabolites of the gut microbiota fermentative process, which have the potential to control intestinal inflammatory processes. This work investigated the intestinal anti-inflammatory activity of dietary green fruits of Musa spp. AAA in the trinitrobenzenesulfonic acid (TNBS) model of intestinal inflammation using three different experimental designs: acute, subchronic, and chronic inflammation with relapse. The results revealed that 10% Musa dietary supplementation significantly attenuated the colonic damage induced by TNBS, as made evident by both histological and biochemical evaluations. This beneficial effect was associated with colonic oxidative status improvement based on Musa spp. AAA prevention of glutathione depletion and inhibition of myeloperoxidase activity. In addition, Musa effects were associated with decreased pro-inflammatory cytokines (IL-1β, TNF-α, IL-6, IL-17, and INF-γ) and gut microbiota modulation, increasing colonic SCFAs production. In conclusion, the intestinal anti-inflammatory activity exerted by Musa spp. AAA was related to its antioxidant, immune, mucosal healing, and gut microbiota modulation properties.